Characteristics and factors controlling reservoir space in the Cretaceous volcanic rocks of the Hailar Basin, NE China. (March 2018) - Zheng, Han; Sun, Xiaomeng; Zhu, Defeng; Tian, Jingxiong; Wang, Pujun; Zhang, Xuqing
Abstract: We discuss the types, capacity, formation mechanisms, and main controlling factors of oil and gas reservoir spaces in Early Cretaceous acidic volcanic rocks of the Hailar Basin, NE China, where asphalt-bearing volcanic rocks are exposed at the surface. We have made systematic observations and analyses on macroscopic (outcrop) and microscopic (optical microscope, SEM, and fluorescence analyzer) scales. Acidic volcanic reservoirs contain reservoir spaces comprising primary and secondary porosity, which are dependent on primary and secondary processes during their formation. Primary porosity typically accounts for a large contribution to enhanced reservoir quality. More importantly, it is a prerequisite for migration, alteration, and filling by inorganic fluids and petroleum, which provides a foundation for the development of secondary porosity. The development of secondary porosity, especially alteration-related pores, can significantly modify the petrophysical characteristics of a rock. In addition to the processes of porosity formation, the quality of volcanic reservoirs is influenced by factors such as lithology, lithofacies, and tectonism. Lithological differences result in variations in the type and intensity of pore development. Pyromeride and glassy lava commonly exhibit high reservoir capacities. The porosity of different lithofacies typically follows the order of conduit facies > extrusive facies > effusive facies > explosive facies. Tectonism is necessary for the formation of reservoir spaces and for the migration, permeation, and accumulation of oil and gas. Reservoir quality is often positively correlated with the size and density of tectonic fractures. Graphical abstract: Image Highlights: Acidic volcanic reservoirs contain primary and secondary reservoir spaces. Primary porosity provides a foundation for the development of secondary porosity. Alteration can significantly modify the petrophysical characteristics of a rock. Pyromeride may be considered the most favorable target. The quality of volcanic reservoirs is governed by lithology, lithofacies, process of porosity formation, and tectonism.